Organisation des pratiques de covoiturage entre inconnus dans les territoires - Elodie Castex (Netcom)
Carpooling systems are now increasing in the French mobility due to the rise of environmental concerns and the development of the Information and Communication Technologies (ICT). Transportation policy now promotes sustainable mobility like carpooling. Using a database of carpooling trip, established in 2012, the aim of the paper is to analyze carpooling mobility inner French territories and especially based on the example of the Lille Metropolitan Area. Carpooling trips will be studied at different scales in order to understand how carpooling complete public transportation system.